PKM Penggunaan SPSS untuk Olah Data dalam Penelitian bagi Guru-Guru SMK Al-Kautsariyyah Mranggen, Demak - Wulandari, Dewi; Handayanto, Agung; Purwati, Heni; Aini, Aurora Nur (Perkumpulan Kualitama Edukatika Indonesia, 2023)
SPSS is a very user-friendly statistical software. Because of its simplicity that makes it very applicable among researchers. So that in this service activity, the team will provide training on the use of SPSS for Al Kautsariyyah Vocational School teachers to use in data processing in classroom action research. The lack of statistical knowledge among teachers in schools is what motivated us to provide SPPS training so that later it is hoped that it will provide sufficient provisions to assist teachers with research, especially quantitative research. In this activity the team provided an introduction to statistical methods and how to apply them in quantitative research using SPSS software. The output form of this community service activity is the product of data processing and its interpretation by the participants. This PKM activity went very well and even had quite a good impact on the participants because the participants gained hands-on experience of SPSS to conduct data processing and analysis in quantitative research. Participants are not only able to operate SPSS, but are also able to interpret the results or output produced by SPSS.